Cryptic divergence in and evolutionary dynamics of endangered hybrid Picea brachytyla sensu stricto in the Qinghai-Tibet Plateau - Shengming Lu; Lian Liu; Weixiao Lei; Donglei Wang; Hui Zhu; Qing Lai; Liru Ma; Dafu Ru (BMC Plant Biology)
Abstract Background The visual similarities observed across various plant groups often conceal underlying genetic distinctions. This occurrence, known as cryptic diversity, underscores the key importance of identifying and understanding cryptic intraspecific evolutionary lineages in evolutionary ecology and conservation biology. Results In this study, we conducted transcriptome analysis of 81 individuals from 18 natural populations of a northern lineage of Picea brachytyla sensu stricto that is endemic to the Qinghai-Tibet Plateau. Our analysis revealed the presence of two distinct local lineages, emerging approximately 444.8 thousand years ago (kya), within this endangered species. The divergence event aligns well with the geographic and climatic oscillations that occurred across the distributional range during the Mid-Pleistocene epoch. Additionally, we identified numerous environmentally correlated gene variants, as well as many other genes showing signals of positive selection across the genome. These factors likely contributed to the persistence and adaptation of the two distinct local lineages. Conclusions Our findings shed light on the highly dynamic evolutionary processes underlying the remarkably similar phenotypes of the two lineages of this endangered species. Importantly, these results enhance our understanding of the evolutionary past for this and for other endangered species with similar histories, and also provide guidance for the development of conservation plans.